Weak protein–cationic co‐ion interactions addressed by X‐ray crystallography and mass spectrometry. (1st August 2014) - Bénas, Philippe; Auzeil, Nicolas; Legrand, Laurent; Brachet, Franck; Regazzetti, Anne; Riès‐Kautt, Madeleine
<x xml:space="preserve">Abstract</x> The adsorption of Rb+, Cs+, Mn2+, Co2+ and Yb3+ onto the positively charged hen egg‐white lysozyme (HEWL) has been investigated by solving 13 X‐ray structures of HEWL crystallized with their chlorides and by applying electrospray ionization mass spectrometry (ESI‐MS) first to dissolved protein crystals and then to the protein in buffered salt solutions. The number of bound cations follows the order Cs+ < Mn2+≃ Co2+ < Yb3+ at 293 K. HEWL binds less Rb+ (qtot = 0.7) than Cs+ (qtot = 3.9) at 100 K. Crystal flash‐cooling drastically increases the binding of Cs+, but poorly affects that of Yb3+, suggesting different interactions. The addition of glycerol increases the number of bound Yb3+ cations, but only slightly increases that of Rb+. HEWL titrations with the same chlorides, followed by ESI‐MS analysis, show that only about 10% of HEWL binds Cs+ and about 40% binds 1–2 Yb3+ cations, while the highest binding reaches 60–70% for protein binding 1–3 Mn2+ or Co2+ cations. The binding sites identified by X‐ray crystallography show that the monovalent Rb+ and Cs+ preferentially bind to carbonyl groups, whereas the multivalent Mn2+, Co2+ and Yb3+ interact with carboxylic groups. This work elucidates the basis of the effect of the Hofmeister cation series on protein solubility.